The contribution of informal learning in the integration process of immigrants into the labour market: Individual and organisational perspectives in selected sectors - Silvia Annen (International Journal of Training and Development, 2023)
In Germany and Canada, the integration of immigrants into the labour market is closely related to the various approaches towards the recognition and validation of informal learning. This paper aims to analyse the informal learning measures undertaken by immigrants as well as those offered by employers in the health and information and communication technology sectors during the labour market integration process. The study focused on nurses as well as IT~project managers and programmers. The comparison focuses on the occurrence and quality of the four dimensions of the dynamic model of informal learning from an individual and an organisation perspective. The results show similarities between these two perspectives regarding the relevance of the four dimensions in the integration of immigrants into the labour market. In addition, clear differences between the two investigated sectors as well as country-specific differences appear.
Keywords: 650